Breeding potential of Pentalonia nigronervosa f. caladii Van der Goot (Homoptera: Aphididae) on katte escape cardamom (Elettaria cardamomum Maton) plants - Anandaraj, M N VENUGOPAL, M J MATHEW, M (Journal of Spices and Aromatic Crops, 1999)
Two viral diseases of cardamom (Elettaria cardamomum) namely, mosaic or katte disease and vein clearing or kokke kandu disease are transmitted by the cardamom aphid, Pentalonia nigronervosa f. caladii. The breeding potential of this vector on 17 mosaic disease escape accessions of cardamom was compared with, those of a local susceptible check. The aphids colonised and multiplied on all test accessions at a rate of multiplication ranging from 1.77 to 3.93, on the 5th day after introduction, On the 10th day after introduction, the local check recorded the highest multiplication rate (5.88) followed by NKE-5 (5,63); NKE-27 recorded the lowest rate of multiplication (2,31). Colonisation of aphids on all katte escape lines indicates that the resistance of cardamom accessions to katte virus is not due to deterrence to vector but due to some other host factors,